Effects of choline metabolite—trimethylamine N-oxide on immunometabolism in inflammatory bowel disease - Wang, Siyu; Ni, Yifan; Zhou, Shuwei; Peng, Huiping; Cao, Ying; Zhu, Yue; Gong, Jing; Lu, Qiulu; Han, Zhongyu; Lin, Yumeng; Wang, Yaodong (Frontiers in Immunology, 2025)
Trimethylamine N-oxide (TMAO), a key metabolite derived from the gut microbial metabolism of choline, has recently been implicated as a significant contributor to the development of several chronic diseases, including diabetes, cardiovascular disease, and chronic kidney disease. Its detrimental effects have garnered widespread attention in the scientific community. Inflammatory bowel disease (IBD), marked by persistent and recurring gastrointestinal inflammation, is a significant global health issue. Emerging evidence highlights a critical role for TMAO in the pathogenesis of IBD. This review comprehensively summarizes current research on the association between TMAO and IBD, with a particular focus on the mechanisms by which TMAO regulates immunometabolism in diseases.